The Peculiarities of the Mention of Mosquitoes in the Qur'an from the Perspective of Tafsir Al-Azhar - Amru Farkhan Salim; Yeti Dahliana; Muhammad Ndow (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to analyze the mention of mosquitoes in QS. Al-Baqarah verse 26 through Tafsir Al-Azhar by Buya Hamka, and explores the relevance of the symbolism to modern scientific knowledge. Theoretical framework: This study combines two approaches: classical interpretations, especially the Al-Azhar Interpretation, which interprets mosquitoes as a symbol of Allah's greatness, and scientific approaches that highlight biology, ecology, and the role of mosquitoes in public health. Literature review: The literature review includes Al-Azhar's interpretation of symbolism in the Qur'an as well as scientific literature on the biology and ecological role of mosquitoes, including their impact on health as a vector of disease. Method: Qualitative method is used with a literature study approach. Data were obtained from the analysis of the text of the Qur'an, Tafsir Al-Azhar, and related scientific literature.  Results:  The study found that Hamka views mosquitoes as a symbol of God's greatness and as a medium of spiritual education. Scientifically, mosquitoes have complex biological structures and play an important role in ecosystems and public health. Implications: This research connects revelation and science, enriching understanding of the role of God's creation, both from a spiritual and scientific perspective, and providing moral lessons about humility. Novelty:  This research integrates the interpretation of the Qur'an with modern science, demonstrates the relevance between religious symbolism and scientific phenomena, and opens up new insights into understanding the relationship between revelation and human knowledge.